BERLIAN (Berkah Limbah Durian): Pemanfaatan Limbah Kulit Durian Menjadi Tepung untuk Meningkatkan Produksi Industri Pempek Rumahan di Desa Patalagan, Kecamatan Pancalang, Kabupaten Kuningan - Mariam Ulfah; Like Efriani; Wiwin Widayanti; Ismanurrahman Hadi (I-Com: Indonesian Community Journal, 2024)
Patalagan Village is one of the largest durian producers in Kuningan City. Many of the bark is thrown into waste. This waste contains compounds that have antibacterial and antioxidant activities. This waste will be useful if developed, including being used as flour for pempel materials. So this activity is called BERLIAN (Berkah Limbah Kulit Durian). The partner in this service is the Bu Odah pempek industry located in Patalagan Village. The purpose of this program is to provide counseling on the health benefits of durian skin, provide training in making durian peel flour and training in making durian peel pempek. The method carried out is socialization, counseling and training in making durian peel pempek. The result of this service is an increase in partners' understanding of the health benefits of durian skin, an increase in partners' ability to make durian peel flour and durian peel pempek. The conclusion of this service activity is that durian peels can be used as a useful product so as to reduce durian peel waste, especially in Patalagan village.